Structural identification and evaluation for SHM applications - Chan, T.; Li, Jun; Caprani, C. (Springer, 2018)
Optimal condition monitoring, maintenance and management of the existing civil infrastructure have been identified as a critical factor in ensuring and raising the economic productive capacity. Direct in-service structural health monitoring and vibration behaviour measurement data are essential to provide more accurate performance assessment and capacity estimation. The main focus of this special issue, organised by Australian Network of Structural Health Monitoring (ANSHM), is to present recent developments and applications of innovative techniques for structural modelling, structural identification with uncertainties, data interpretation for structural performance prediction and reserve capacity evaluation.